Willingness to communicate in Chinese: Foreign students studying abroad in Beijing - Wan, Huiwen (2017)
This paper attempts to look into the factors affecting willingness to communicate (WTC) in a local language that is not the individual’s first language, specifically overseas college students currently studying Mandarin in Beijing. The research was carried out in Beijing with five participants who all had Chinese learning background. The results indicated that the antecedents of their second language (L2) WTC vary and not all the suggestions from previous studies were supported. This could be owing to the fact that the group of college students in Beijing have specific needs or characteristics that were not covered in previous studies. This qualitative research has a small sample size which makes it difficult to generalize to the students’ WTC in other parts of China. However, the findings might have enlightenments for teaching and further research.